NH2-truncated human tau induces deregulated mitophagy in neurons by aberrant recruitment of Parkin and UCHL-1: implications in Alzheimer's disease - Corsetti, V.; Florenzano, F.; Atlante, A.; Bobba, A.; Ciotti, M.T.; Natale, F.; Della Valle, F.; Borreca, A.; Manca, A.; Meli, G.; Ferraina, C.; Feligioni, M.; et al. (Human molecular genetics, 2015)
Disarrangement in functions and quality control of mitochondria at synapses are early events in Alzheimer's disease (AD) pathobiology. We reported that a 20-22 kDa NH2-tau fragment mapping between 26 and 230 amino acids of the longest human tau isoform (aka NH2htau): (i) is detectable in cellular and animal AD models, as well in synaptic mitochondria and cerebrospinal fluids (CSF) from human AD subjects; (ii) is neurotoxic in primary hippocampal neurons; (iii) compromises the mitochondrial biology both directly, by inhibiting the ANT-1-dependent ADP/ATP exchange, and indirectly, by impairing their selective autophagic clearance (mitophagy). Here, we show that the extensive Parkin-dependent turnover of mitochondria occurring in NH2htau-expressing post-mitotic neurons plays a pro-death role and that UCHL-1, the cytosolic Ubiquitin-C-terminal hydrolase L1 which directs the physiological remodeling of synapses by controlling ubiquitin homeostasis, critically contributes to mitochondrial and synaptic failure in this in vitro AD model. Pharmacological or genetic suppression of improper mitophagy, either by inhibition of mitochondrial targeting to autophagosomes or by shRNA-mediated silencing of Parkin or UCHL-1 gene expression, restores synaptic and mitochondrial content providing partial but significant protection against the NH2htau-induced neuronal death. Moreover, in mitochondria from human AD synapses, the endogenous NH2htau is stably associated with Parkin and with UCHL-1. Taken together, our studies show a causative link between the excessive mitochondrial turnover and the NH2htau-induced in vitro neuronal death, suggesting that pathogenetic tau truncation may contribute to synaptic deterioration in AD by aberrant recruitment of Parkin and UCHL-1 to mitochondria making them more prone to detrimental autophagic clearance.